2020
DOI: 10.1016/j.ausmj.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Consumption: Three Consumer Segment Views

Abstract: As consumers are moving away from mindless consumerism, a mindful consumption literature has emerged that is based on Buddhist and psychological perspectives of mindfulness. While the idea of mindful consumption has great potential, there is little empirical research to date that comprehensively examines the consumer perspective on the role of mindfulness on consumption. To provide a grounded consumer perspective, the authors segment mindful consumption views from open-end text using a mixed method of clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 38 publications
5
79
0
Order By: Relevance
“…In a qualitative study of more than 500 essays about consumers' understanding of 'mindful consumption', researchers examined if the engagement in mindfulness practices comes with a shift in consumer values and priorities (Milne et al 2019). Milne et al (2019) identified three segments of 'mindful' consumers: those with a (1) consumer first view, a (2) firm observer view and (3) an informed consumer view. While the first consumer segment included the smallest number of mindful practitioners, it stands for a mostly economic and qualityoriented perspective on mindful shopping.…”
Section: Personal Values and Ethical Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative study of more than 500 essays about consumers' understanding of 'mindful consumption', researchers examined if the engagement in mindfulness practices comes with a shift in consumer values and priorities (Milne et al 2019). Milne et al (2019) identified three segments of 'mindful' consumers: those with a (1) consumer first view, a (2) firm observer view and (3) an informed consumer view. While the first consumer segment included the smallest number of mindful practitioners, it stands for a mostly economic and qualityoriented perspective on mindful shopping.…”
Section: Personal Values and Ethical Decision-makingmentioning
confidence: 99%
“…While the first consumer segment included the smallest number of mindful practitioners, it stands for a mostly economic and qualityoriented perspective on mindful shopping. The other views, where mindfulness practitioners were more frequently represented, showed greater involvement with sustainability issues and the monitoring of company practices (Milne et al 2019).…”
Section: Personal Values and Ethical Decision-makingmentioning
confidence: 99%
“…There is also an intangible facet of the mentality about the behaviors, beliefs, and perceptions underlying consumption actions (Dhandra, 2019). The mentality matters in two crucial ways: attitudes and values affect consumer preferences, and they also decide how the impact from consumption is perceived, thus increasing or decreasing the probability of a related nature's further consumption (Milne et al, 2020). To address the issue of over-consumption effectively, both actions and attitudes need to change.…”
Section: Mindful Consumptionmentioning
confidence: 99%
“…Literature circumscribed the motivating factors influencing the intention to buy SHC; however, it still does not understand why and how such factors contribute to buying intentions (Luo et al, 2020). Recent developments in psychology and neuroscience believe mindful consumption will open new pathways to sustainability (Milne et al, 2020). However, the role of mindful consumption in environmental mitigation has been overlooked, and related academic studies barely emerged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation